Estudio de factibilidad de una operadora turística que incida en el desarrollo turístico de la parroquia Cojimíes - Zambrano Lucas, Karol Lisbeth (2019)
The research was carried out with the objective of studying the feasibility for a tour operator in Cojimíes parish, which allows promoting tourism development in the area, with priority as tourist enjoyment, optimal use of resources and job creation in the location. The type of research was exploratory and descriptive. The development of the research was structured in 4 phases: in the first, a tourist diagnosis was made, where general and tourist data were obtained that determined the current situation of the place of study. In the second phase, a market study was carried out where it was found that the demand is mostly framed by tourists from the mountains, in a minimum percentage, international; it has a wide range of accommodation, 35 being the total number of establishments, with less presence of restaurants that are 7, as well as the competition is differentiated by the volume of the visitor and technological facilities. In the third phase, a portfolio of 3 tourism products directed towards the obtained market segment was developed, in the same way marketing mix strategies were proposed. In the last phase, the feasibility of the operator was evaluated, the same one that contemplated the organizational structure, defining the professional profile and their respective functions, the engineering of the project and the financial feasibility through the VAN evaluation indexes ($2,995.92) and the IRR (21%), determining that the development of the project is feasible.